Light Emission Properties of 2D Transition Metal Dichalcogenides: Fundamentals and Applications. Issue 21 (5th August 2018) - Zheng, Weihao; Jiang, Ying; Hu, Xuelu; Li, Honglai; Zeng, Zhouxiaosong; Wang, Xiao; Pan, Anlian
Abstract: 2D transition metal dichalcogenides (2D TMDs) with energy bandgaps covering the visible and near infrared spectral region have enormous advantages in various photonic and optoelectronic applications, such as light emitting devices, transistors, photovoltaic devices, photodetectors, and nanocavity lasers. Understanding the mechanisms and controlling the optical properties of 2D TMDs is of crucial importance for further applications in integrated photonics. This review focuses on the light emission properties of 2D TMDs and their heterojunctions (HJs), including the fundamentals, tunability, and device applications. The band structures and excitonic properties related to light emission in 2D TMDs are discussed. The approaches to control, tune, and enhance light emission are also discussed. Subsequently, the light emission phenomena in 2D TMD HJs and their mechanisms associated with interlayer exciton, charge transfer, and energy transfer processes are described. Finally, the future potentials and challenges in TMD photonics are presented. Abstract : This review is focused on the light emission properties of 2D transition metal dichalcogenides (2D TMDs), including their fundamental properties, tunability, and device applications. The band structures and excitonic properties regarding light emission are discussed. Approaches to control, tune, and enhance the light emission are also presented. The light emission phenomena and their mechanisms in 2D TMD heterojunctions are described.